International Developments in Skills Migration: A Case Study of the Opportunities, Threats and Dilemmas for Australia - Kell, P.; Cameron, Roslyn; Joyce, D.; Wallace, M. (Springer, 2014)
Skilled migration is not a particularly new phenomenon, however it has become much relied upon by many nations both sending and hosting in an ever increasing global economy. This chapter explores the international trends in relation to the global mobility of workers and professionals before taking a case study approach which examines the opportunities, threats and dilemmas facing Australia and its use of skilled migration. First we look at Australia’s migration policies and recent changes in these which support a demand driven model before exploring Australia’s skill shortages with particular reference to the Australian rail industry.